2013
DOI: 10.1007/s10803-013-1812-0
|View full text |Cite
|
Sign up to set email alerts
|

Respite Care, Marital Quality, and Stress in Parents of Children with Autism Spectrum Disorders

Abstract: Parents of children with autism spectrum disorders (ASD) are at risk for having higher stress and lower marital quality than other parents. Survey data regarding respite care, marital quality, and daily hassles and uplifts were obtained from 101 mother-father dyads who were together raising at least one child with ASD (total # of children = 118). Number of hours of respite care was positively related to improved marital quality for both husbands and wives, such that a 1-h increase in weekly respite care was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 46 publications
1
76
1
7
Order By: Relevance
“…The increased chaos seen in families of children with ASD may also contribute to increased parental conflict and decreased marital satisfaction seen in these families (Brobst et al 2009;Gau et al 2011;Harper et al 2013;Hartley et al 2011). The presence of emotional strain and relationship difficulties likely make it more difficult for children with ASD to learn appropriate social behaviors, as more maladaptive interactions are modeled by caregivers who are frequently engaged in conflict.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…The increased chaos seen in families of children with ASD may also contribute to increased parental conflict and decreased marital satisfaction seen in these families (Brobst et al 2009;Gau et al 2011;Harper et al 2013;Hartley et al 2011). The presence of emotional strain and relationship difficulties likely make it more difficult for children with ASD to learn appropriate social behaviors, as more maladaptive interactions are modeled by caregivers who are frequently engaged in conflict.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…In fact, a recent review on coping styles among parents of children with ASD reported that age and gender of parents are the most commonly discussed factors (Lai & Oei, 2014). Spousal relationship factors, such as spousal support (Dunn, Burbine, Bowers, & Tantleff-Dunn, 2001), marital satisfaction (Higgins, Bailey, & Pearce, 2005), and marital quality (Harper, Dyches, Harper, Roper, & South, 2013), are other parental characteristics used to investigate the experiences of parents of children with ASD. Parents of children with ASD were found to experience spousal relationship issues when they used maladaptive coping strategies, such as escape-avoidance (Dunn et al, 2001).…”
mentioning
confidence: 99%
“…The same tendency has been observed in Russia; e.g., statistics (2015) on cerebral palsy in children reported an increment in the number of new cerebral palsy cases diagnosed annually from 6854 in 2013 to 7734 in 2014 [2]. In turn, children with special needs have a transformative effect on their families as a whole and each family member, especially mothers [3][4][5][6]. Recent studies have shown that there is a considerable decrease in psychological well-being among mothers raising children with special needs [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 68%